Cross border, highly individualised treatment of a patient with challenging extensively drug-resistant tuberculosis. Issue 3 (22nd March 2018) - Akkerman, Onno W.; Grasmeijer, Floris; de Lange, Wiel C.M.; Kerstjens, Huib A.M.; de Vries, Gerard; Bolhuis, Mathieu S.; Alffenaar, Jan-Willem; Frijlink, Henderik W.; Smith, Grace; Gajraj, Roger; de Zwaan, Rina; Hagedoorn, Paul; et al.
Extensively drug-resistant (XDR) tuberculosis (TB) is defined by resistance to isoniazid, rifampicin, any fluoroquinolone and at least one of the three second line injectable drugs, such as amikacin. Drug toxicity and duration impair adherence to treatment and outcome is rather poor [1]. We report on a particularly challenging XDR-TB patient with persistent non-adherence to treatment and an exceptionally complex drug susceptibility pattern. Crossing borders by treating a patient with difficult to treat XDR-TB; highly individualised but holistic approach http://ow.ly/JyjK30ielsD